(untitled) (Research, Society and Development, 2024)
This text presents a scoping review protocol that seeks to map and analyze academic-scientific production regarding the repercussions of CNE/CES resolution nº 6/2018 on the initial training of teachers, as established by the current National Curricular Guidelines for teaching courses. Degree in Physical Education from 2019 to 2023. The Scope Review protocol aims to document and describe the organization and structure of pre-planned processes for preparing review reports, allowing for the systematization and transparency of procedures. The study follows the methodological guidelines according to the guidelines of the Joanna Briggs Institute (JBI) organization and the reference of the guide for reporting following the items of the Preferred Reporting Items for Systematic Review - Scoping Review (PRISMA-ScR). The PCC (Population, Concept and Context) strategy guided the search for information that will be carried out in the databases of SciElo, LILACS, Brazilian Digital Library of Theses and Dissertations (BDTD), CAPES Journal Portal and Google Scholar. The data will be extracted into a form with information and presented in table format. This protocol will assist in the development of the scoping review to identify the effects of curricular policies on subject training and gaps in the field of teacher training in Physical Education. The protocol has been registered with the Open Science Framework (OSF).